The influence of question format on accuracy of children’s testimony - Čėsnienė, Ilona (Psichologija, 2004)
A number of investigators have suggested that children, even preschoolers, can in fact recall a great deal of information accurately, but there are some important limitations, especially, question format. While analysing this limitation, it is important to state how the syntax of a question is related to the accuracy of narration and how investigators should formulate questions in order to get accurate and reliable responses. Moreover, the structure of a sentence influences the perception of a question and syntax in Lithuanian differs from Germanic languages, therefore it has been unclear whether the results of such investigations can be applied to the Lithuanian situation. Accordingly, the goal of the present study was to investigate the influence of question format on preschool-aged childre’s accuracy of narrative in different interviews. Whereas some studies have also showed that the content of information investigated (action, people, environment) is of great importance for the accuracy of children’s narrative, the influence of the content of informatikon was investigated in this study too. Children aged 6 to 7 years took part in a Christmas event. Three weeks later children were interviewed about the event for the first time; questions asked were of different format (open- and close-ended). Four months later the interview was repeated, some questions from the first interview were asked. Children’s accuracy of narration was estimated by two psychologists. The study showed that question format substantially influenced children’s responses: children frequently responded „I don’t know“ to open-ended questions, they were most likely to make errors if asked closeended questions. Therefore it is recommended to ask children more often open-ended questions, especially if the interview is repeated. Furthermore, it should be mentioned that children recalled less important details with greater difficulty in comparison with personally important information. More detailed analysis proved that the accuracy of narration depends on the content: the most accurate answers were given about actions, environment and verbal information were described less accurately. The difference in accuracy was statistically significant. Therefore it is recommended to ask young children more questions about actions.